Incremental housing as a node for intersecting flows of city-making: rethinking the housing shortage in the global South. (April 2020) - Van Noorloos, Femke; Cirolia, Liza Rose; Friendly, Abigail; Jukur, Smruti; Schramm, Sophie; Steel, Griet; Valenzuela, Lucía
Incremental housing drives urbanization worldwide, and is recognized as the basis for socially relevant solutions to housing shortages in the global South. However, scholarship on incremental housing continues to focus largely on tenure, building materials and housing conditions at a local level, while incremental housing is embedded in – and dependent on – larger urban and regional systems and flows. We argue that a further reconceptualization of incremental housing is needed that acknowledges the embeddedness of local incremental building practices within broader industries, markets and practices of city-making. Starting from this observation, we suggest an extended framework for understanding the city-wide industries and flows around incremental housing, in relation to five dimensions: 1) land, 2) finance, 3) infrastructure, 4) building materials and 5) labour. Mapping these dynamics is necessary to understand fundamental questions of where, how and why initiatives aimed at improving or developing incremental housing advance or get stuck.